Educating a Multilingual Workforce in Chinese universities: Employability of Master of Translation and Interpreting Graduates - Wu 吴赟, Yun; Jiang 姜智威, Zhiwei (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This article examines the employability of Master of Translation and Interpreting (MTI) graduates in China, where globalized exchanges have led to an increasing need for translation education in recent decades; however few studies have assessed the employment of MTI graduates. To that end, we have surveyed all the MTI alumni that graduated between 2015 and 2020 from one first-tier university in Shanghai using a questionnaire based on a comprehensive employability measurement model. By processing the collected questionnaire data in a quantitative manner, we illustrate the industrial distribution of the employed MTI graduates and identify the core assets constituting their employability needed to work in different industries. Via comparisons between our inquiry results and the current enrollment and curricular design of MTI programs, we further argue that the actual market for MTI graduates is experiencing a surplus and that MTI curricula have not completely met the employability requirements in various industries and professions. The conclusion herein implies a nationwide revision of China’s MTI programs, which may include the control of student enrollment and updated syllabi catering to the employability requirements in China’s workplaces.